2015
DOI: 10.14227/dt220115p36
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a BioequivalenceIndicating Dissolution Specification for Candesartan Cilexetil Tablets Using a Convolution Model

Abstract: The aim of the present work was to establish a bioequivalence-indicating dissolution specification for candesartan cilexetil tablets. The discriminating power of the selected medium (0.25% Polysorbate 20 in pH 6.5 phosphate buffer) was assessed relative to that of 0.35% Polysorbate 20 in pH 6.5 phosphate buffer, a medium recommended by the U.S. FDA. Plasma concentration-time profiles of candesartan cilexetil tablets were derived from in vitro dissolution data by a convolution model. In solubility studies, 0.25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…In such cases, the addition of surfactants helps to obtain sink conditions, by enabling the drug release process at the solid-liquid interface and micelle solubilization in bulk 34 and is recommended for performing in-vitro dissolution studies 35,36 .…”
Section: Discussionmentioning
confidence: 99%
“…In such cases, the addition of surfactants helps to obtain sink conditions, by enabling the drug release process at the solid-liquid interface and micelle solubilization in bulk 34 and is recommended for performing in-vitro dissolution studies 35,36 .…”
Section: Discussionmentioning
confidence: 99%
“…In-vitro release study was achieved for all formulations in addition to pure CC suspension. The release condition monitored in 0.1 M HCl (pH 1.2) and PBS (pH 6.8) and at the same conditions with adding tween 20 (0.35%-0.7%w/w) to achieve "sink" conditions during a dissolution test for all formulations 54,55 . It was found that all formulations exhibit a lack of drug release within 24 h. The in-vitro release of the best formula (CC-NLC9) was reached to less than 5% as showed in (figure 6) but, CC suspension showed almost complete drug release (100%) within 8 h. As CC had solubility equal to 11 μg/ml in 0.1 M HCl and 1 μg/ml in PBS (pH 6.8).…”
Section: In-vitro Release Studymentioning
confidence: 99%
“…Hydrophobic APIs will display absorption kinetics based on the rate-limiting step of dissolution, and those APIs with insufficient permeability will demonstrate permeation -rate limited absorption kinetics [1]. Noyes-Whitney equation suggests that the aqueous solubility of an API is directly related to the its rate of dissolution and consequently it is a significant variable that regulates the rate of dissolution and thereby the absorption [2].…”
Section: Introductionmentioning
confidence: 99%